The Amount of Different Forms of Iron Contained in Soils Formed in Tertiary Reddish Deposits (Texas Journal of Multidisciplinary Studies, 2022)
In this work, the amount of various forms of iron in soils formed on tertiary red-colored deposits is compared with typical serozems formed on lyossian deposits, by horizons and levels of erosion. It has been established that the gross, silicate and nocilicate forms of iron in the soil are determined as a percentage of the soil mass.